The radar signature of the Wind Lens: a less disruptive wind turbine? - Balleri, Alessio; Al-Armaghany, A.; Griffiths, Hugh D.; Tong, Kenneth; Matsuura, Takashi (Cranfield University, 2013)
We study the radar signature of a new type of wind turbine, named the Wind Lens. This design includes a flanged shroud around the turbine which concentrates the wind flow past the turbine blades and hence improves the efficiency. The design also offers improved safety, and reduces acoustic noise. Furthermore, it may offer a significantly lower radar signature, which may make the design much more attractive for use in situations where conventional wind turbine designs may disturb the operation of radars. We present the results of an experimental trial, carried out in the UK, to measure the Radar Cross Section (RCS) of a 5 kW Wind Lens turbine prototype and we provide a reference database that can be used for comparing the Wind Lens RCS with that of conventional turbines. We investigate methods to further reduce the Wind Lens RCS and present the results of a time-varying Doppler analysis. Results show that the addition of a metallic mesh around the shroud obscures the rotating blades, and hence mitigates the RCS by 15 dBm2, at angles where the radar interference is highest.
Keywords: Radar systems; Wind turbines